Edukasi Peningkatan Gizi pada Ibu Hamil di Wilayah Kerja UPT Puskesmas Kampung Sawah Kota Bandar Lampung - Rilyani Rilyani; Marlina Agustina; Refsi Erpiyana; Asep Rahmat Hidayat; Alisah Rahmah Hidayah; Dina Martiani; Imanda Satria; Sastria Handayani (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Pregnancy is the most important period in a woman's life cycle. During pregnancy, a woman provides nutrition not only herself, but also herself and the fetus. Pregnant women should be careful with their food intake. You not only need to consume enough food and drinks, but they also need to be balanced and contain enough nutrients. Non-compliance with nutrition during pregnancy causes malnutrition, the worst impact of which is incomplete fetal growth, low birth weight (LBW), and fetal abnormalities. The aim of this activity is to increase respondents' knowledge regarding the nutrition of pregnant women. It was found that respondents were very enthusiastic about listening to the material presented by the presenters. The nutritional status of a pregnant woman before and during pregnancy can affect the development of the fetus she is carrying. If a mother's nutritional status is normal before and during pregnancy, she will most likely give birth to a healthy adult child with a normal weight